Diseño e implementación de un sistema automático para el control de acceso al parqueadero Nº1 del campus Matriz de la Universidad Técnica de Cotopaxi - Cunalata Licto, Edgar Mauricio (2017)
This research Project is based on the designing and implementation an automatic system by the Access control to the parking Nº 1 of main campus at Technical University of Cotopaxi, this permits to view from the guardroom at the real time free space in the parking, the expensive cost of the best technology to this process and the faster space researching by the guard, he/she must verify into it, and this produce a busy car traffic when they want to enter in it, is realized a researching in the camp through the view after that researching step by step in the automatic place, that need permits to diagnose the determined area and the time that needs the responsible person to do this process, that identifies the time although a topographic process determination the strategies points to put the sensors that identify the cars at the same time, also we emphasize the electric designing, to the purpose to do an automatic system as a simple, practical way for the user, that permits to obtain a low prices in the market, motivating at the same time to apply a new knowledge for the technological innovated parking system, this will reduce the busy car at the time that we needed to look for the parking space, and by this way it is possible to view the free spaces faster and certain form, according to the determined results as possible.